Empowering communities to manage natural resources: where does the power lie?: the case of Malawi - Kayambazinthu, D. (2000)
Effective community-based natural resource management (CBNRM) has been practiced for decades in Malawi where traditional leaders command much power over their subjects. Political and economic changes over the years have weakened the powers of the local leaders, and made it difficult for them to mobilise their people towards CBNRM. A multi sectoral approach by a number of players, aimed at capacity building combined with strong traditional leadership and appropriate legal framework would provide the necessary conditions to restore community confidence and commitment for successful CBNRM. This paper describes such a process.